Guidelines for the diagnosis, prevention and management of implantable cardiac electronic device infection. Report of a joint Working Party project on behalf of the British Society for Antimicrobial Chemotherapy (BSAC, host organization), British Heart Rhythm Society (BHRS), British Cardiovascular Society (BCS), British Heart Valve Society (BHVS) and British Society for Echocardiography (BSE) - Sandoe, Jonathan A. T.; Barlow, Gavin; Chambers, John B.; Gammage, Michael; Guleri, Achyut; Howard, Philip; Olson, Ewan; Perry, John D.; Prendergast, Bernard D.; Spry, Michael J.; Steeds, Richard P.; Tayebjee, Muzahir H.; et al. (Journal of antimicrobial chemotherapy, 2015)
Infections related to implantable cardiac electronic devices (ICEDs), including pacemakers, implantable cardiac defibrillators and cardiac resynchronization therapy devices, are increasing in incidence in the USA and are likely to increase in the UK, because more devices are being implanted. These devices have both intravascular and extravascular components and infection can involve the generator, device leads and native cardiac structures or various combinations. ICED infections can be life-threatening, particularly when associated with endocardial infection, and all-cause mortality of up to 35% has been reported. Like infective endocarditis, ICED infections can be difficult to diagnose and manage. This guideline aims to (i) improve the quality of care provided to patients with ICEDs, (ii) provide an educational resource for all relevant healthcare professionals, (iii) encourage a multidisciplinary approach to ICED infection management, (iv) promote a standardized approach to the diagnosis, management, surveillance and prevention of ICED infection through pragmatic evidence-rated recommendations, and (v) advise on future research projects/audit. The guideline is intended to assist in the clinical care of patients with suspected or confirmed ICED infection in the UK, to inform local infection prevention and treatment policies and guidelines and to be used in the development of educational and training material by the relevant professional societies. The questions covered by the guideline are presented at the beginning of each section.